KURIKULUM BERBASIS KOMPETENSI (Konsep Dasar dan Implementasi) - Moh Rifai (Universitas PGRI Madiun, 2012)
In effort of the nation surival, a society need a set of educations which are then termed as competence so as to be proffesional, competitive and merit. The basic competence has become the substance of success in live and living. The breakdown of the nation’s economy, education, culture and also monetary affairs is not due to the lack of the government power, rather a lack of the basic competence possessed by the political actors, which needs to be questioned. Unfortunately, the prosperity of Indonesian nature can not bring Indonesia to become the master in our own nation, but it does them poverty due to live under pressure of other nation. It has been caused by the lack of the basic competence of our nation in managing, preserving, utilizing the nation’s prosperity.